2020
DOI: 10.1177/1471301220971630
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation and decision-making in persons with dementia: A scoping review

Abstract: Background and Objectives Emotion is integral to decision-making, and emotion regulation is associated with improved well-being in older age. Persons with dementia are likely to experience impairments in emotion regulation processes that can potentially contribute to differential decision-making and well-being outcomes. To promote the development of theoretical models of well-being in dementia, we review the quantitative evidence concerning the associations between emotion regulation and decision-making in dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…Factor 5, “Valuing enjoyment and relationships with others”, included various items, such as “Doing what I love and having fun” and “Being energetic and feeling good”. Yamamoto-Mitani et al raised control of emotion as a subscale of the QOL scale for older patients suffering from dementia [ 19 ], and Perach et al pointed out that the control of emotions is crucial in decision making among older patients suffering from dementia [ 20 ]. These findings suggest that among older adults with declining cognitive functions, it is crucial to maintain a good emotional status by valuing enjoyment and relationships with others to ensure the maintenance of self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Factor 5, “Valuing enjoyment and relationships with others”, included various items, such as “Doing what I love and having fun” and “Being energetic and feeling good”. Yamamoto-Mitani et al raised control of emotion as a subscale of the QOL scale for older patients suffering from dementia [ 19 ], and Perach et al pointed out that the control of emotions is crucial in decision making among older patients suffering from dementia [ 20 ]. These findings suggest that among older adults with declining cognitive functions, it is crucial to maintain a good emotional status by valuing enjoyment and relationships with others to ensure the maintenance of self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Factor 2 has four items that reflect actions taken by care staff to assist OwDs with communication (e.g., “we wait for the OwD to respond, even if their communication takes time, to draw the terms for their daily living” and “to form a will, we support them to make their choices independently and show concrete choices in their daily living according to their pace”). For ACP, individuals with moderate and severe dementia, especially OwDs, may have difficulty with verbal communication; thus, it is important to better understand their current quality of life, fears, and desires by responding to their emotions, paying attention to nonverbal communication, and observing their behavior [ 13 ]. It has also been reported that emotional control is important for decision-making in OwDs [ 14 ], and the communication of care preferences and assisting with communication correspond to Factors 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…They argue for 'an approach to emotion that conceives of emotional processes as intimately tied up with agency' (Slaby, Paskaleva, and Stephan 2013, 34) but explore how this relationship can result in an 'impairment of agency' in conditions such as depression (ibid, 42). This understanding could inform discussions around agency in dementia as agency is seen as something that can fluctuate and be affected by emotional states as well as cognitive impairment 2,3 Perach et al have demonstrated how emotions and our ability to regulate them play an important role in decision-making (Perach et al 2021)…”
Section: Emotionsmentioning
confidence: 99%